Nickel-Catalyzed Asymmetric Reductive Heck Cyclization of Aryl Halides to Afford Indolines - Qin, Xurong (2018)
A nickel‐catalyzed asymmetric reductive Heck reaction of aryl chlorides has been developed that affords substituted indolines with high enantioselectivity. Manganese powder is used as the terminal reductant with water as a proton source. Mechanistically, it is distinct from the palladium‐catalyzed process in that the nickel–carbon bond is converted into a C−H bond to release the product through protonation instead of hydride donation followed by C−H reductive elimination on Pd.